IMPLEMENTASI PROGRAM JAMINAN KESEHATAN NASIONAL (JKN) DI PROVINSI BENGKULU - Rahayu, Desita; Sasman, Sasman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2017)
The government has integrated all kind of health programs into one stakeholder Social Security Administrator for Health (BPJS Kesehatan) since 2014. The new program must provide health service for all layers of citizens. The more layers must be organized the more complicated problem arise. JKN can be implemented well if it has sufficient resources. BPJS kesehatan handles membership activity and manages budgeting, meanwhile the human resources who deliver health service belongs to the health facilities. Street level buraucrats in health service in RSUD dr. M. Yunus Bengkulu are the object of this research. Based on Ripley and Franklin’s theory, there are three dominant ways to measure successful public policy implementation such as the degree of compliance, smoothly functioning routines and the absence of problems, and desired performance and impacts. This research is in qualitative method. The result of the research shows that this program runs well, street level bureaucrats obey the rules and INA CBG’s system in treating the patient. There are compliements and complaints related to the health service. The compliements come from those who feel satisfied. Complaints come not only from the unsatisfied patient but also from the health service provider such as nurse, doctor, who do not have the space to do discretion. They are insisted to obey the new system in delivering health service